How to Write Abstracts for Health Research Articles ? - Joel Rey U. Acob (Humanistic Network for Science and Technology (HNST), 2017)
Abstract writing is very important, because good abstract is one of the determining factors for the passing of an article submission to scientific journals, proceedings, and other publication media. In this journal (Health Notions) it is also explicitly communicated in the menu of